2014
DOI: 10.1002/jsfa.6941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high temperature on grain filling period, yield, amylose content and activity of starch biosynthesis enzymes in endosperm of basmati rice

Abstract: Results suggest changes in amylose/amylopectin ratio observed in plants grown at 32 °C was attributable to a reduction in activity of GBSS, the sole enzyme responsible for amylose biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
95
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 46 publications
8
95
3
Order By: Relevance
“…We observed that heat stress significantly decreased the Q enzyme and IAA in the spikelets in both genotypes, but higher reduce were shown in superior spikelet than inferiors. This changing pattern was similar to the temperature difference between the superior and inferior spikelets under heat stress, suggesting that the key enzymes including Q enzyme and IAA in spikelets were susceptible to heat stress, which had been confirmed by the previous results (Jin et al, 2005; Tang et al, 2008; Ahmed et al, 2015). Additionally, the greater reduction in the content of IAA shown in superior spikelets induced by heat stress could reduce the apical-grain superiority to mediate grain-filling in inferior spikelets (Wang et al, 2001, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…We observed that heat stress significantly decreased the Q enzyme and IAA in the spikelets in both genotypes, but higher reduce were shown in superior spikelet than inferiors. This changing pattern was similar to the temperature difference between the superior and inferior spikelets under heat stress, suggesting that the key enzymes including Q enzyme and IAA in spikelets were susceptible to heat stress, which had been confirmed by the previous results (Jin et al, 2005; Tang et al, 2008; Ahmed et al, 2015). Additionally, the greater reduction in the content of IAA shown in superior spikelets induced by heat stress could reduce the apical-grain superiority to mediate grain-filling in inferior spikelets (Wang et al, 2001, 2003).…”
Section: Discussionsupporting
confidence: 83%
“…These results are in line with previous reports (Piper and Boote 1999;Thomas et al 2003) in which the starch and soluble sugar contents in soybean seeds were found to decrease with rise in temperature. Similar correlations have been observed in other crops such as rice (Ahmed et al 2015) and wheat (Rijven 1986;Zhao et al 2006;Yan et al 2008;Liu et al 2011). The reasons for this phenomenon were supposedly the lower activities of starch synthase, ADP-glucose pyrophosphorylase, starch phosphorylase, and soluble starch synthase enzymes involved in sucrose to starch conversion at higher temperatures (Rijven 1986).…”
Section: Discussionsupporting
confidence: 60%
“…In other way, AGPase has been also considered as a key enzyme participating in the starch synthesis, and its activity is associated with rate and quantity of starch synthesis (Ahmadi & Baker, 2001;Yang et al, 2004;Yang et al, 2017). AGPase at the early grain filling stage were decreased as result of supra-optimal temperatures (Ahmed et al, 2015); under other abiotic stress, as such water deficit, SuSase and AGPase had its activities levels influenced. Our results suggest that the bigger capacity of N22 to maintain higher soluble sugar levels (fructose, glucose and sucrose) at milk stage can have contributed to their better yield component stability across night temperatures imposed.…”
Section: Discussionmentioning
confidence: 99%